Neural controller for flexible robotic manipulator - Raveendran, N. (2008)
A dynamic model of a two-link flexible robot was derived and simulations were carried out to analyze the flexibility of the manipulator. The Langrangian approach and assumed mode shapes are utilized to develop the dynamic model of the two-link flexible robotic manipulator. It was found that the flexibility of the manipulator results in the vibration of links. Conventional controllers such as PD Controller, inverse controller and inverse controller with Direct Strain Feed Back (DSFB) were used to eliminate these vibrations. Simulations were carried out to analyze the control of vibration of both rigid and flexible manipulators. Satisfactory results were obtained for all controllers on rigid manipulator, but on flexible manipulator, only inverse controller with direct strain feedback displayed satisfactory results. An analysis was also carried out to determine the effects of parameter variation on the control of vibrations of the flexible manipulator.